Effects of Muscarinic Acetylcholine 3 Receptor208-227 Peptide Immunization on Autoimmune Response in Nonobese Diabetic Mice - Lin Yang; Jinzhe Ju; Wei Zhang; Fengfeng Lv; Chunyan Pang; Guoan Yang; Yongfu Wang (Clinical and Developmental Immunology)
The second extracellular loop (LFWQYFVGKRTVPPGECFIQFLSEPTITFGTAI, aa 205–237) of muscarinic acetylcholine 3 receptor (M3R) has been reported to be an epitope for autoantibodies generated during certain autoimmune disorders, including Sjögren’s syndrome (SS). Autoantibodies against M3R228–237 have been shown to interfere with the function of M3R. However, few studies have been performed on the M3R205–227 peptide of the second extracellular loop. In the current study, we sought to investigate the effect of M3R208–227 peptide immunization on autoimmune response in NOD/LtJ mice. We synthesized the M3R208–227 peptide and immunized NOD/LtJ mice to investigate whether peptide-specific antibodies could be generated and whether immunization would lead to changes in autoimmune response in NOD/LtJ mice. Our results demonstrate that the secretions of Th-1, Th-2, and Th-17 cytokines are downregulated and lymphocytic infiltration is improved in the salivary glands and lacrimal glands following immunization with M3R208–227 peptide in NOD/LtJ mice, suggesting that peptide immunotherapy using the M3R208–227 peptide may represent a potential therapeutic alternative.